Markers of the denormalisation of smoking and the tobacco industry. (24th January 2008) - Chapman, S; Freeman, B
Abstract : Background: In nations with histories of declining smoking prevalence and comprehensive tobacco control policies, smoking-positive cultures have been severely eroded. Smoking, smokers and the tobacco industry are today routinely depicted in everyday discourse and media representations in a variety of overwhelmingly negative ways. Several authors have invoked Erving Goffman's notions of stigmatisation to describe the process and impact of this radical transformation, which importantly includes motivating smoking cessation. Efforts to describe nations' progress toward comprehensive tobacco control have hitherto taken little account of the role of cultural change to the meaning of smoking and the many ways in which it has become denormalised. Methods: This paper identifies a diversity of generally undocumented yet pervasive markers of the "spoiled identity" of smoking, smokers and the tobacco industry, illustrated with examples from Australia, a nation with advanced tobacco control. Results: We caution about some important negative consequences arising from the stigmatisation of smokers. Conclusions: We recommend that schemes rating the comprehensiveness of national tobacco control should be supplemented by documentation of markers of this denormalisation.